IMPLEMETASI TPB, RISK TOLERANCE DAN FINANCIAL LITERACY TERHADAP P2P LENDING DI SURAKARTA - Lika, Efliani Enga; Kristyana Dananti (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2022)
Investment Intention is influenced by various factors, such as psychological factors, the benefits obtained as well as the ease of operations carried out and knowledge of finances. The researcher feels the need to develop the previous research so that the researcher takes the theory of planned behavioural variable which includes attitude toward behavioural, subjective norm and perceived behavioural control, risk tolerance and financial literacy using 96 respondents. Data processing was carried out using the SPSS statistical test. The results of this test show that attitudes toward behavioural and subjective norms have significant and positive effects on investment intention in peer to peer lending in Surakarta partially. Perceived behavioural control, risk tolerance and financial literacy partially have no significant effect on investment intention in peer to peer lending in Surakarta. But simultaneously has a significant effect. So it can be concluded that attitude to word behavioural, subjective norm, perceived control behaviour, risk tolerance and financial literacy still influence on investment interest so it needs to be a concern.